2003
DOI: 10.1385/endo:21:1:89
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estradiol, Phytoestrogens, and Ginkgo Biloba Extracts Against 1-Methyl-4-phenyl-pyridine-Induced Oxidative Stress

Abstract: Oxidative stress has been recently considered as a mediator of nerve cell death in several neurodegenerative diseases. We studied the effect of the parkinsonism-inducing toxine 1-methyl-4-phenyl-pyridine (MPP+) on several parameters of cell distress using native and neuronal PC12 cells. Then, since estrogens have been reported to prevent neuronal degeneration caused by oxidative damage, we investigated the ability of 17beta- estradiol (E2); two Ginkgo biloba extracts, EGb 761 and Cp 202; as well as two flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…As described in the introduction section, treatment with quercetin at 5-40 mM attenuated cell death induced by various causes of oxidative stress such as MPP ϩ , H 2 O 2 and b-amyloid peptides in neuronal cells including differentiated PC12 cells. 6,15,20) We found that quercetin did not protect against H 2 O 2 toxicity, but by itself caused cell death accompanied by DNA fragmentation in undifferentiated PC12 cells. The reasons for this discrepancy are not clear at present.…”
Section: Possible Mechanism Of Quercetin-induced Cell Toxicitymentioning
confidence: 90%
See 3 more Smart Citations
“…As described in the introduction section, treatment with quercetin at 5-40 mM attenuated cell death induced by various causes of oxidative stress such as MPP ϩ , H 2 O 2 and b-amyloid peptides in neuronal cells including differentiated PC12 cells. 6,15,20) We found that quercetin did not protect against H 2 O 2 toxicity, but by itself caused cell death accompanied by DNA fragmentation in undifferentiated PC12 cells. The reasons for this discrepancy are not clear at present.…”
Section: Possible Mechanism Of Quercetin-induced Cell Toxicitymentioning
confidence: 90%
“…25) Quercetin showed a protective effect against MPP ϩ toxicity in differentiated, but not in undifferentiated, PC12 cells. 15) These reports may indicate that the response to quercetin differs depending on the degree of cell differentiation. In our conditions, however, quercetin caused cell death of differentiated PC12 cells.…”
Section: Possible Mechanism Of Quercetin-induced Cell Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…These observations led to the conclusion that the neuroprotective effects of 17a-E2 or 17b-E2 might be due to their antioxidant properties, although other non-genomic effects could not be excluded. Regardless, 17b-E2, 17a-E2, and the phytoestrogens quercetin and resveratrol, all protect PC12 cells against MPP1, whereas closely related molecules with less extended resonance structure, such as coumestrol, genistein, and kaempferol, do not [Gelinas and Martinoli, 2002;Gagne et al, 2003]. Despite the studies that report comparable cytoprotection by the two estradiol isomers in cell culture, only 17b-E2 has demonstrated beneficial effects in the animal models of PD, such as MPTP toxicity [Dluzen et al, 2001;Ramirez et al, 2003;Callier et al, 2000Callier et al, , 2002.…”
Section: Introductionmentioning
confidence: 98%